Sound stimulus effects on dusky damselfish behavior and cognition. (November 2022) - de Souza, Jessica F.; Silveira, Mayara M.; Barcellos, Heloisa H.A.; Barcellos, Leonardo J.G.; Luchiari, Ana C.
Abstract: Anthropogenic noises are widespread and affect marine wildlife. Despite the growing knowledge on noise pollution in the marine environment, its effects on fish cognition are scarce. Here, we investigated the effects of sound exposure on anxiety-like behavior and memory retention on dusky damselfish Stegastes fuscus . The animals were trained in a conditioned place aversion task, and exposed to two daily sessions of music at intensities of 60–70 dBA or 90–100 dBA, while the control group was kept at 42–46 dBA (no music) for five days. After that, fish were tested in the novel tank paradigm and tested for the memory of the aversive task. In the novel tank, animals exposed to sound spent more time still and decreased the distance from the bottom of the tank. Animals also spent more time on the aversive side of the conditioning tank. These results suggest that anthropogenic noise applied through high-intensity music can increase anxiety and decrease memory retention in S. fuscus, suggesting the deleterious potential of noise for reef species. Graphical abstract: Unlabelled Image Highlights: Anthropogenic noise generated outside the water impacts damselfish behavior. Music intensity between 60 and 100 dBA increased fish anxiety-like behavior. 5-Day memory retention was impaired by music noise.